SMART CHILD SECURITY SYSTEM BASED ON IoT - Dhanalakshmi, R; Shiba, C.Mary (International Journal of Computer Sciences and Engineering, 2025)
Nowadays child security is an important area of concern. This model is developed to rectify the worries of parents regarding their child security. This paper proposed a model for child safety through smart phones that provides the option to track the location of their children as well as in case of emergency notification is send via E-mail.Mobile phones can be used to enhance student’s services. One of these services is taking the attendance. Taking attendance requires a location factor of the student. Hence, iBeacon can be used for this purpose. iBeacon is not only used for marking attendance it is also used for location a child who roaming inside the school campus. The exact location and the time how long he/she spend in that location is transferred to the class teacher.Automated learning analytics is becoming an important topic in the educational community, which needs effective systems to monitor learning process and provide feedback to the teacher and parent. Student affective states such as happy, sad, fear, disgust, surprise, angry, neutral are automatically determined from facial expressions.